Studi Komposisi Resin Phenolic Sebagai Bahan Matrik Dalam Pembuatan Kampas Rem Metode Campuran Kering - Yulqa, Lanang Bagus (2016)
Brake pad is one coumponent of a motor vehicle that serves to slow ora stop the vehicle, especially ground.When a high-speed vehicle brake has an important role in such a deep, even the salvation of a soul riders depending on the quality of the brake lining. The purpose of research is to test the use of phenolic resins as a replacement for epoxy resin matrik material in the manufacture of brake lining, with materials such as brass powder, aluminium powder, carbon ,barium sulfat, cacium carbonate , fiber glass. Manufacture brake on tap with a load of7,5tonsfor7minutes in the oven for60minutesat a temperature of 200 °C. Testing was conducte on the swipe test and hardnees test. The use of phenolic resin mixture variatiaon of21,9% has lowest wear rate compared with a mixture of 17,4% and 26,1%. This can be proved in any of the testing process frictional wear rate of the mixture 21,9% is equal 4,3 mm3/minute for the dry testing, 3,5 mm3/minute on water testing and 3,1 mm3/minute on oil testing.The test result showed that the quality of the brake lining wet method is still better than the brake mixture of dray methods. This can be proved in mixture of 17,4% higher wear rate in comparison with the wet mixture.